An Overview of Corporate Social Responsibility Ads from a Critical Perspective: A Critical Discourse Analysis of The Finish Water of Tomorrow Advertising Campaign - Demirci, Kenan (Springer Nature, 2023)
Corporate social responsibility (CSR) covers the activities carried out by companies to protect the social resources necessary for their survival. According to liberal approaches stemming from Friedman’s arguments concerning responsibility, the idea of protecting the economic interests of the company is more important than the responsibility of the company to society. On the other hand, critical approaches point to the fact that given the importance placed on information conveyed by advertisements, the use of criteria like profitability instead of social responsibility can cause problems, such as the spreading of misinformation. In this context, the study focuses on how the information is used in advertisements on CSR activities. To do this, six advertisements broadcast by Finish Turkey as part of the campaign Water of Tomorrow were analyzed by critical discourse analysis in three categories: text, context, and discourse. As a result of the study, it was concluded that the ads deal with the problem in a very narrow frame and identify the solutions only to the consumer. This result shows us that social responsibility advertising should not be viewed as unconditionally positive. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2022.
Keywords: Corporate social responsibility; Corporate social responsibility advertisements; Critical discourse analysis